Adsorptive removal of tetracycline from aqueous solutions using magnetic Fe2O3 / activated carbon prepared from Cynometra ramiflora fruit waste. (January 2023) - Selvaraj, Raja; Prabhu, Deepa; Kumar, P. Senthil; Rangasamy, Gayathri; Murugesan, Gokulakrishnan; Rajesh, Mouli; Goveas, Louella Concepta; Varadavenkatesan, Thivaharan; Samanth, Adithya; Balakrishnaraja, R.; Vinayagam, Ramesh
Abstract: Herein, the sustainable fabrication of magnetic iron oxide nanoadsorbent prepared with activated carbon of inedible Cynometra ramiflora fruit has been investigated. Activated carbon was obtained from phosphoric acid-treated C . ramiflora fruit, which was then utilized for the synthesis of magnetic nanocomposite (CRAC@Fe2 O3 ). The formed nanocomposite was a porous irregular dense matrix of amorphous evenly sized spherical nanoparticles, as visualized by FESEM, and also contained carbon, oxygen, iron, and phosphorous in its elemental composition. FT-IR spectrum depicted characteristic bands attributing to Fe–O, C–OH, C–N, CC, and –OH bonds. VSM and XRD results proved that CRAC@Fe2 O3 was superparamagnetic with a moderate degree of crystallinity and high saturation magnetization value (1.66 emu/g). Superior surface area, pore size, and pore volume of 766.75 m 2 /g, 2.11 nm, and 0.4050 cm 3 /g respectively were measured on BET analysis of CRAC@Fe2 O3 nanocomposite, indicating their suitability for use as an adsorbent. On application of this nanocomposite for adsorption of tetracycline, maximum removal of 95.78% of 50 ppm TC at pH 4, CRAC@Fe2 O3 0.4 g/L in 240 min. The adsorption of TC by CRAC@Fe2 O3 was confirmed as monolayer sorption by ionic interaction ( R 2  = 0.9999) as it followed pseudo-second-order kinetics and Langmuir isotherm ( R 2  = 0.9801). CRAC@Fe2 O3 showed a maximum adsorption capacity of 312.5 mg/g towards TC antibiotics indicating its potential for the treatment of antibiotic-contaminated samples. Since negative Δ G o and positive Δ H o and Δ S o values were obtained at all tested temperatures during the thermodynamic studies, the adsorption was confirmed to be endothermic, spontaneous, and feasible with an enhanced degree of randomness. Graphical abstract: Image 1 Highlights: Magnetic activated carbon was synthesised using  Cynometra ramiflora  fruit biomass. Irregular dense matrix of spherical Fe2 O3  were seen in FESEM image. High specific surface area of 766.75 m 2 /g with mesopores were obtained. TTetracycline adsorption using magnetic activated carbon with 312.5 mg/g was obtained.